Clinical outcomes of mandibular body fracture management using wire-reinforced intraoral composite splints in 15 cats - Pakula, Joanna; Freeman, Alix; Perry, Andrew (Frontiers in Veterinary Science, 2025)
The study assesses the use of wire-reinforced intraoral composite splints (WRICS) for stabilising mandibular body fractures in feline patients. It reviews 15 cases treated at a referral centre, focusing on the effectiveness of WRICS in achieving stable fracture repair, occlusion, and patient comfort. The fractures were most commonly between the canine tooth and third premolar (73%). Results indicate that WRICS can provide effective stabilisation with a median healing time of 8 weeks. Normocclusion was achieved in 14 out of 15 cases. Major complications were found in two cases (13%) and were associated with soft tissue ulceration. This study supports WRICS as a minimally invasive, reliable approach to mandibular body fracture stabilisation in cats.